Kesehatan Mental Petani Selama Masa Pandemi COVID-19 di Kabupaten Bondowoso - M. Elyas Arif Budiman; Zidni Nuris Yuhbaba; Irwina Angelia Silvanasari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Mental health problems among farmers were identified as population health problems. Farmers' mental health can have an impact on individual health, family life, farm productivity, and the health and welfare of farmer groups. In recent years, the economic outlook for farmers has deteriorated due to the COVID-19 pandemic which has directly affected farmers' mental health. The design of this research is explanatory survey with cross sectional approach. The population of this research is farmers in Bondowoso Regency. The sample size of 149 respondents was recruited using simple random sampling technique. The instrument used in this study was a mental health inventory questionnaire. The data used in this research is descriptive statistical analysis so that the results will be obtained in the form of frequency distribution. Data analysis aims to obtain a picture of the mental health of farmers while facing the impact of the COVID-19 pandemic. The results of the calculation of descriptive data of mental health variables in the table above show that of the 149 respondents, around 95 respondents are under psychological pressure, 63.8% and psychological well-being around 44 respondents 36.6%. The conclusion of this study is that the farmer population experiences various kinds of psychological disorders. and soul caused by various things including aspects of working as a farmer and personal problems related to family and society. Some predictors of psychological problems in this study are the impact of COVID-19 which affects the agricultural sector. Keyword: mental health; farmer; Covid-19ABSTRAKMasalah kesehatan mental di kalangan petani diidentifikasi sebagai masalah kesehatan penduduk. Kesehatan mental petani dapat berdampak pada kesehatan individu, kehidupan keluarga, produktivitas usaha tani, serta kesehatan dan kesejahteraan kelompok tani. Dalam beberapa tahun terakhir, prospek ekonomi bagi para petani memburuk akibat Pandemi COVID-19 yang secara langsung memepengaruhi kesehtan mental petani. Desain penelitian ini adalah eksplanatory survey dengan pendekatan cross sectional. Populasi penelitian ini adalah Petani diKabupaten Bondowoso. Besar sampel 149 responden direkrut dengan teknik simple random sampling. Instrumen yang digunakan pada penelitian ini adalah Kuesioner mental health inventory. Data yang digunakan dalam penelitian ini adalah analisis statistik deskriptif sehingga akan didapatkan hasil dalam bentuk distribusi frekuensi. Analisis data bertujuan untuk memperoleh gambaran kesehatan mental petani selama mengahadapi dampak pandemi COVID-19. Hasil perhitungan data deskriptif variabel kesehatan mental pada tabel diatas menunjukkan bahwa dari 149 responden, berada pada tekanan psikologis sekitar 95 responden 63,8% dan kesejahteraan psikologis sekitar 44 responden 36,6% Kesimpulan dari penelitian ini adalah bahwa populasi petani mengalami berbagai macam gangguan psikologis dan gangguan mental yang disebabkan berbagai hal termasuk aspek dalam pekerjaan sebagai petani dan masalah personal terkait dengan keluarga maupun masyarakat. Beberapa prediktor terjadinya masalah psikologis pada penelitian ini adalah adanya dampak COVID-19 yang mempengaruhi pada sektor pertanian.Keywords: kesehatan mental; petani; Covid-19